The effect of fibroblast growth factors and advanced glycation end-products on the intima-media complex thickness in patients with coronary heart disease and type 2 diabetes - Ekaterina Vladimirovna Ivannikova; Victor Yurievich Kalashnikov; Olga Mikhailovna Smirnova; Alexander Borisovich Kuznetsov; Anatolievich Terekhin; Alexander Viktorovich Il'in (Сахарный диабет)
Objective. To determine the levels of fibroblast transforming growth factor (TGF?1), basic fibroblast growth factor (?-FGF), markers of nonspecific inflammatory response (interleukin-6 (IL-6)), C-reactive protein (CRP), advanced glycation end-products (AGEs) and their receptors (RAGEs) and to study their effect on the intima-media complex (IMC) thickness in patients with coronary heart disease (CHD) and type 2 diabetes, depending on carbohydrate metabolism compensation. Materials and Methods. 37 patients with CHD underwent a general clinical examination, analysis of the carbohydrate and lipid metabolism parameters and the renal function, and also were evaluated with instrumental methods of analysis (echocardiography, coronary angiography and duplex scanning of the brachiocephalic arteries). To determine the level of the analyzed parameters, blood samples were taken from the aorta during coronary angiography and concomitantly from the cubital vein in all patients. Results. The presence of diabetes mellitus (DM) in patients with CHD was found to be associated with a more severe atherosclerotic disease of the coronary and brachiocephalic vessels. A direct correlation between the degree of stenosis and the level of fibroblast growth factors, inflammatory factors, and advanced glycation end-products was found. A direct correlation between AGE and TGF?1 and the lipid metabolism parameters was established. A statistically significant elevation of the studied parameters in the arterial and venous blood of patients with DM was revealed. Conclusion. These findings confirm the relationship between connective tissue disorders and lipid metabolism in the pathogenesis of atherosclerosis. A negative effect of hyperglycaemia on atherosclerotic changes of the vascular wall was demonstrated.